Ahura a modular multi-functional bed that will increase the efficiency of a singular room residence - Cheock, Margaret Elsa G.
The growing market for small condominium units has now presented modern person with a new dilemma. This is because of the tiny space available inside these shoebox units which customers have to bear due to budget constraints. A shoebox unit is defined as condominiums or apartments having only up to 50 square meters in dimensions. With this issue in mind, there is a need for space and cost efficient furniture to improve the quality of lives of people using these shoebox units. Ahura is a modular multi-functional bed that will increase the efficiency of a singular room residence for millenial residents. It is also designed to make its transport from place to place more convenient. Ahura transforms as a bed, workplace, and sala set with plenty of storage capacity designed into its parts to maximize space and functionality.